New Biomarkers Used in the Diagnosis of Tuberculosis-Related Pleural Effusions - Teke, Turgut (Journal of Pediatric Infectious Diseases, 2020)
Tuberculosis-related pleural effusion (TPE) is reported in 12 to 38% of thoracic tuberculosis (TB) cases in the pediatric population. In TPE, the pleural fluid bacilli load is very low, generally resulting in negative acid-fast bacill (AFB) staining and Mycobacterium culture. In the pleural fluid, AFB stain positivity is reported in <20%, and Mycobacterium tuberculosis positive culture in 18 to 38%. In childhood, this ratio is even lower. Also, pleural effusion (PE) mycobacterial culture gives late results (2–8 weeks). Therefore, TPE is diagnosed with pleura biopsy and pleural liquid examination. However, pleura biopsy is a more invasive operation and the diagnosis rates vary. The clinical and laboratory findings are not typical; it is very hard to distinguish between TPE and another cause of exudative PE. This situation makes it essential for research on reliable new biomarkers that can provide fast and accurate diagnosis of TPE. Adenosine deaminase (ADA) activity being above 40 to 50 U/L (despite varying depending on age) strongly suggests TPE. Other new biomarkers featured in TPE diagnosis are interferon-γ, cytokines, and nucleic acid multiplication tests. However, the results of ADA and other potential biomarkers shown to be beneficial in TPE diagnosis should always be interpreted with clinical and microbiological findings because no biomarker can provide information about M. tuberculosis culture and drug resistance. Especially in countries with high resistance against TB drugs, performing pleura biopsy, culture and drug resistance tests are important with regard to diagnosis and therapy planning.
Keywords: tuberculosis-related pleural effusion; new biomarkers; adenosine deaminase